Capitalizing on co-benefits and synergies to promote the blue economy in Asia and the Pacific - Masanori Kobayashi; Atsushi Watanabe; Keita Furukawa; Keshia N. Tingson; Cielito F. Habito (Asian Development Bank Institute (ADBI), 2021)
A blue economy has become a pivotal policy objective to promote sustainable development through the conservation and sustainable use of marine and coastal resources. An approach to promote co-benefits and synergies is useful for a wide range of stakeholders. To articulate such co-benefits and synergies, the authors chose cases for analysis based on the co-benefits and synergies in the promotion of a sustainable blue economy. They performed a socio-ecological system analysis to examine the interface of marine and coastal ecosystem changes and the policy and institutional responses. In the analyzed cases, the study identified a sound policy framework, multi-stakeholder and cross-sectoral collaboration, innovation, and science-based policy development and implementation as factors that catalyzed co-benefits and synergies. On the other hand, market disruption, changes in the marine environment, and climate change impacts impeded the efforts to promote a blue economy. The results of the analysis demonstrated that capacity development and international partnership are indispensable to promote a blue economy and scale up this effort. The analysis also inferred that research institutes can play a role in providing policy options and courses of action to assess the locally available resources and pursue co-benefits and synergies through the conservation and sustainable use of marine and coastal resources with the aim of achieving a sustainable blue economy.
Keywords: Q; 330; blue economy; co-benefit; synergies; trade-offs; innovation; partnership